2013
DOI: 10.1007/s00268-013-2260-x
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Nerve Monitoring Can Reduce Prevalence of Recurrent Laryngeal Nerve Injury in Thyroid Reoperations: Results of a Retrospective Cohort Study

Abstract: BackgroundThe prevalence of recurrent laryngeal nerve (RLN) injury is higher in repeat than in primary thyroid operations. The use of intraoperative nerve monitoring (IONM) as an aid in dissection of the scar tissue is believed to minimize the risk of nerve injury. The aim of this study was to examine whether the use of IONM in thyroid reoperations can reduce the prevalence of RLN injury.MethodsThis was a retrospective cohort study of patients who underwent thyroid reoperations with IONM versus with RLN visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
148
3
10

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(162 citation statements)
references
References 44 publications
1
148
3
10
Order By: Relevance
“…IONM of the RLN and the external branch of the superior laryngeal nerve (EBSLN) have been standardized and seem to be beneficial in high risk thyroid operations, particularly in reoperations (25,26). In recent years there have been many publications concerning the introduction of IONM, the learning curve and the technical aspects of new the technology, and assessing the prevalence of complications when utilizing IONM (17,20,(25)(26)(27)(29)(30)(31)(32). But very little data concerning the incidence of RLN injury in reoperations with IONM has been published, and only a few publications have compared the RLN injury rate during secondary thyroid surgery using IONM with procedures using only visual RLN identification (16)(17)(18)(19)33,34).…”
Section: Review Articlementioning
confidence: 99%
See 2 more Smart Citations
“…IONM of the RLN and the external branch of the superior laryngeal nerve (EBSLN) have been standardized and seem to be beneficial in high risk thyroid operations, particularly in reoperations (25,26). In recent years there have been many publications concerning the introduction of IONM, the learning curve and the technical aspects of new the technology, and assessing the prevalence of complications when utilizing IONM (17,20,(25)(26)(27)(29)(30)(31)(32). But very little data concerning the incidence of RLN injury in reoperations with IONM has been published, and only a few publications have compared the RLN injury rate during secondary thyroid surgery using IONM with procedures using only visual RLN identification (16)(17)(18)(19)33,34).…”
Section: Review Articlementioning
confidence: 99%
“…Barczyński et al showed that almost 20% of the RLNs were identified with IONM before visual exposition of the nerve, and almost twice as many ramified nerves were identified in reoperations with IONM than without monitoring (P<0.001) (17). Moreover, the use of IONM significantly (P=0.02) improved identification of non-recurrent laryngeal nerves (non-RLNs) than in operations without monitoring (17). In a scarred operating field there can be problems with hemostasis because of the high degree of vascularization.…”
Section: Rln Identification and Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…(13,14), bazÖ çalÖ malarda ise tiroidektomi sÖ-rasÖnda sinir monitörü kullanÖmÖnÖn önceki cerrahilere ba lÖ anatominin bozuldu u yüksek riskli hastalarda tavsiye edilse de UVKP geli me riskini azaltmadÖ ÖnÖ göstermi tir (15)(16)(17).…”
Section: Methodsunclassified
“…Although there are studies suggesting that intraoperative nerve monitoring decreased injury rates, many studies comparing IONM and nerve dissection did not reveal any superiority of the methods over each other (11)(12)(13)(14). In 2007, Dralle et al (15) stated that not using IONM was considered as malpractice in several lawsuits.…”
Section: Discussionmentioning
confidence: 99%